2022
DOI: 10.2478/raon-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

Various clinical presentations of uveitis associated with durvalumab treatment

Abstract: Background Immune checkpoint inhibitors (ICI) are becoming increasingly common in treating several cancer types. Durvalumab is a human IgG1 monoclonal antibody that blocks PD-L1 binding to PD-1 and CD80 and has recently been approved for the treatment of extensive-stage small-cell lung cancer (ES-SCLC) and locally advanced unresectable (NSCLC). The present review aimed to analyse immune-mediated uveitis, secondary to durvalumab treatment, through a review of the literature and a presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Trials on avelumab or talazoparib plus binimetinib in mPDAC have shown promising additive or synergistic antitumor activity. Durvalumab is another humanized IgG1 monoclonal antibody ( 73 ) that targets PD-L1 and activates anti-tumor immunity by blocking the interaction between PD-L1 and its receptor, PD-1. It was first approved by the FDA in 2017 for the treatment of locally advanced or metastatic urothelial carcinoma ( 74 ) and stage III unresectable non-small cell lung cancer ( 75 ).…”
Section: Icismentioning
confidence: 99%
“…Trials on avelumab or talazoparib plus binimetinib in mPDAC have shown promising additive or synergistic antitumor activity. Durvalumab is another humanized IgG1 monoclonal antibody ( 73 ) that targets PD-L1 and activates anti-tumor immunity by blocking the interaction between PD-L1 and its receptor, PD-1. It was first approved by the FDA in 2017 for the treatment of locally advanced or metastatic urothelial carcinoma ( 74 ) and stage III unresectable non-small cell lung cancer ( 75 ).…”
Section: Icismentioning
confidence: 99%